2005
DOI: 10.1016/j.exger.2005.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Cellular senescence in the glaucomatous outflow pathway

Abstract: The mechanisms responsible for the progressive malfunction of the trabecular meshwork (TM)-Schlemm's canal (SC) conventional outflow pathway tissue in primary open angle glaucoma (POAG) are still not fully understood. To determine whether POAG is characterized by an accumulation of senescent cells, similar to what has been described in other diseases, we have compared the levels of the senescence marker senescence-associated-β-galactosidase (SA-β-gal) in the outflow pathway cells of POAG and age-matched contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
106
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(117 citation statements)
references
References 26 publications
5
106
0
2
Order By: Relevance
“…In addition, considering that VEGFC-VEGFR3 signaling plays an essential role in SC formation (8,9) and that Angpt-Tie2 signaling shares this role, it is supposed that there is a close crosstalk between those signaling pathways in SC. Cellular senescence of SC is associated with accumulation of harmful stimuli and reactive oxygen species, which may cause dysfunctional drainage in humans and mice (39,54). Along with the previous report demonstrating decreased AHO and reduced expression of lymphatic markers such as Prox1 and VEGFR3 in aged SC (8), we reveal here that aged SC ECs exhibit attenuated intercellular junctions and decreased cellularity and transcytosis together with an attenuated Angpt-Tie2 system.…”
Section: Tie2 Activation Rejuvenates Aged Sc and Rescues Impaired Scsupporting
confidence: 61%
“…In addition, considering that VEGFC-VEGFR3 signaling plays an essential role in SC formation (8,9) and that Angpt-Tie2 signaling shares this role, it is supposed that there is a close crosstalk between those signaling pathways in SC. Cellular senescence of SC is associated with accumulation of harmful stimuli and reactive oxygen species, which may cause dysfunctional drainage in humans and mice (39,54). Along with the previous report demonstrating decreased AHO and reduced expression of lymphatic markers such as Prox1 and VEGFR3 in aged SC (8), we reveal here that aged SC ECs exhibit attenuated intercellular junctions and decreased cellularity and transcytosis together with an attenuated Angpt-Tie2 system.…”
Section: Tie2 Activation Rejuvenates Aged Sc and Rescues Impaired Scsupporting
confidence: 61%
“…The senescence of SC in aged mice is quite similar to that in aged humans (46). However, there are only few works in the literature depicting the integrity of SC ECs, except decreased densities of transendothelial pores in SC ECs, depending on AHO with aging (56).…”
Section: Preparations and Treatments Of Reagentsmentioning
confidence: 97%
“…Because of its role in regulating energy metabolism and production, GAL may be used as a biomarker for monitoring or restoring the function of optical neural functions. CXCL6 is a cytokine that induces the directed migration of monocytes and neutrophils (Yoshie et al, 2001) and was found to be modulated in glaucoma (Liton et al, 2006;Lukas et al, 2008). Paylakhi et al (2011) further reported that CXCL6 was regulated by pituitary homeobox 2 in glaucoma.…”
Section: Discussionmentioning
confidence: 99%